Density of Hedychium coronarium in 1st order river riparian Forest in an environmental protection area - Marchello, Adriano Evandir; Erica Maria Castilho Martins (Revista Biociências, 2024)
The exotic invasive plant species Hedychium coronarium, which due to its accelerated growth and dispersion ends up replacing native vegetation, was found on the banks of a prime river in an environmental protection area, in the city of Piratininga, state of São Paulo. Quantitative monitoring to calculate the density, diversity, dominance, and evenness of the species in the areas were carried out between August and October 2022. In the sampled areas, differences in the diversity and quantity of plants present were observed, probably related to the luminosity and the soil favoring greater advantage of exotic plants, which are more adapted than native species, in addition to a greater dominance of Hedychium coronarium in areas of lower diversity.